ANTIOXIDANT AND ANTIBACTERIAL ACTIVITIES OF THE PARASITIC PLANTS OROBANCHE FOETIDA AND OROBANCHE CRENATA COLLECTED ON FABA BEAN IN TUNISIA - Z. Abbes1; N. El Abed2; M. Amri; M. Kharrat; S. Ben Hadj Ahmed (Journal of Animal and Plant Sciences, 2014)
The antioxidant activity of the methanolic and aqueous extracts of two parasitic plants Orobanche crenata and Orobanche foetida collected from faba bean fields was investigated with 2 complementary test systems, DPPH (2,2-diphenyl-1-picrylhydrazyl) and ABTS (2,2-azino-bis-3-ethylbenzothiazoline-6-sulfonic acid ) radical scavenging activities.  The O. crenata methanol extract showed the highest level of DPPH and ABTS free radical scavenging activities, with IC50 values of 2.76 µg/ml and 7.96 µg/ml respectively. The amount of total polyphenol and tannins varied in the different plant extracts and ranged from 3.02 to 19.99 mg GAE/g DW for polyphenol contents and from 0.09 to 0.32 mg EC/g DW for tannins contents. Antimicrobial activity was investigated with the disc diffusion method. The methanol extract of O. foetida showed activity against all tested bacterial strains, except S. aureus ATCC 6538, by forming clear inhibition zones with diameters between 12 and 30 mm whereas methanol extracts of O. crenata inhibits only L. monocytogenes and S. enteredis ATCC 502 with an inhibition zone of 10 and 25 mm respectively. Aqueous extracts of the two Orobanche species were not active against any of these bacterial isolates. These results implied that these two Orobanche species collected from infested faba bean fields might be potential resources of antioxidant and antibacterial activities and can be used in human nutrition and some industrial and pharmaceutical products.
Keywords: antioxidant; antibacterial; O. foetida; O. crenata; polyphenol